The Influence Of Consumer Perceptions About Price, Product Quality And Service Quality Towards Purchasing Decisions (at Janji Jiwa Bengkalis) - Yuni Sitta; M Alkadri Perdana (Politeknik Negeri Bengkalis, 2021)
This study aims to determine the relationship and influence of price variables, product quality, service quality on purchasing decisions at the Janji Jiwa cafe in Bengkalis partially and simultaneously, to determine the magnitude of the influence of the price variable, product quality, and service quality on purchasing decisions. This type of research is associative. From the test results using partial and simultaneous tests that the variable price, product quality and service quality have a relationship and influence on purchasing decisions. The test results of the coefficient of determination variable price, product quality and service quality affect purchasing decisions with a value of price (22.8%), product quality (44.5%) and service quality (36.7%). This shows that the influence of price, product quality and service quality variables affect purchasing decisions by 60.8%. While the remaining 39.2% (100% - 60.8%) is explained by other causes.